The Relationship Between Workload Level and the Incidence of Burnout Syndrome Among Nurses in the Surgical Inpatient Ward - Ulil Absor; Betie Febriana; Wahyu Endang (KHD Production, 2025)
Burnout syndrome is a psychological condition characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, which can affect the quality of nursing care. Nurses in surgical inpatient wards are at high risk of experiencing burnout due to the high demands of patient care and heavy workload. This study aimed to analyze the relationship between workload level and the incidence of burnout syndrome among nurses in the surgical inpatient ward of Sultan Agung Islamic Hospital, Semarang. This research employed a quantitative method with a cross-sectional design. The study sample consisted of 118 nurses selected using a total sampling technique. The instruments used were the Nursalam workload questionnaire and the Maslach Burnout Inventory (MBI) to assess burnout syndrome. Data analysis was conducted using the Chi-Square test at a significance level of p < 0.000. The results showed that most respondents had a moderate workload (87.3%) and experienced a high level of burnout (66.9%). Statistical analysis indicated a significant relationship between workload level and the incidence of burnout syndrome (p = 0.000). Nurses with higher workloads tended to experience more severe burnout than those with lighter workloads. These findings emphasize that workload is an important factor influencing burnout among nurses. Therefore, hospital management is advised to implement workload management strategies, increase the number of nursing staff, and provide psychological support programs to reduce the risk of burnout and improve nurses’ well-being and performance.